Catalytic properties of binary and ternary alloys based on silver - Ved, M.; Glushkova, M.; Sakhnenko, N. (Functional Materials, 2013)
The correlation between the morphology, composition and catalytic properties of silver-cobalt alloys has been shown. The galvanic Ag–Co alloy is established as synergetic ones, and the values obtained for the exchange current density of the model hydrogen evolution reaction are similar to platinum. The catalytic activity testing results of binary (Ag–Co) and ternary (Ag–Co–Zr, Ag–Co–Bi) alloys in the carbon monoxide oxidation to carbon dioxide were analyzed.